Sarcoidosis, inorganic dust exposure and content of bronchoalveolar lavage fluid: the MINASARC pilot study - Catinon, Mickael; Cavalin, Catherine; Chemarin, Cécile; Rio, Stéphane; Roux, Elisabeth; Pecquet, Mathieu; Blanchet, Anne-Sophie; Vuillermoz, Sylvie; Pison, Christophe; Arbib, François; Bonneterre, Vincent; Valeyre, Dominique; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Inhalation of mineral dust was suggested to contribute to sarcoidosis. We compared the mineral exposome of 20 sarcoidosis and 20 matched healthy subjects. Bronchoalveolar lavage (BAL) samples were treated by digestion-filtration and analyzed by transmission electron microscopy. The chemical composition of inorganic particles was determined by energy-dispersive X-ray (EDX) spectroscopy. Dust exposure was also assessed by a specific questionnaire. Eight sarcoidosis patients and five healthy volunteers had a high dust load in their BAL. No significant difference was observed between the overall inorganic particle load of each group while a significant higher load for steel was observed in sarcoidosis patients (p=0.029). Moreover, the building activity sub-score was significantly higher in sarcoidosis patients (p=0.018). These results suggest that building work could be a risk factor for sarcoidosis which could be considered at least in some cases as a granulomatosis caused by airborne inorganic dust. The questionnaire should be validated in larger studies.